2022
DOI: 10.3389/fonc.2022.996495
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors in advanced and recurrent/metastatic cervical cancer

Abstract: Cervical cancer (CC) poses a serious threat to women’s health. Although many early-stage patients have a good prognosis, there are still a lack of effective therapies for advanced and recurrent/metastatic CC. In this context, immunotherapy and immune checkpoint inhibitors (ICIs) are particularly likely to play a role in the treatment of cervical tumors in a variety of disease settings. Some promising immune checkpoints include programmed cell death 1 (PD-1), programmed death ligand 1 (PD-L1) and cytotoxic T ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…This is consistent with the clinical observation of CC as an immune-related malignancy with a higher prevalence in immunocompromised patient cohorts [16]. It is also in line with the close relationship between CC oncogenesis and DNA repair defects (dMMR, HRD) leading to the emergence of potentially immunogenic tumor neoantigens [17]. In this context, the ESMO Next Generation Sequencing (NGS) Recommendations had advocated testing of tumor mutational burden (TMB) in cervical cancer patients as early as 2020 [18], given the clinical benefits of checkpoint blockade in patients with dMMR deficiency or high microsatellite instability (MSI-H) observed in the KEYNOTE-158 trial.…”
Section: Introductionsupporting
confidence: 90%
“…This is consistent with the clinical observation of CC as an immune-related malignancy with a higher prevalence in immunocompromised patient cohorts [16]. It is also in line with the close relationship between CC oncogenesis and DNA repair defects (dMMR, HRD) leading to the emergence of potentially immunogenic tumor neoantigens [17]. In this context, the ESMO Next Generation Sequencing (NGS) Recommendations had advocated testing of tumor mutational burden (TMB) in cervical cancer patients as early as 2020 [18], given the clinical benefits of checkpoint blockade in patients with dMMR deficiency or high microsatellite instability (MSI-H) observed in the KEYNOTE-158 trial.…”
Section: Introductionsupporting
confidence: 90%
“…In recent years, immune checkpoint inhibitors (ICIs) have been shown to be one of the most promising and effective immunotherapies, which reconstitute anti-tumor responses and prevent tumor cells from evading immune surveillance by targeting speci c molecules, such as programmed death receptor 1 (PD-1) or its ligand (PD-L1) and cytotoxic T-lymphocyte antigen 4 (CTLA-4) [52][53][54]. Our current ndings suggest that TOP2A is involved in regulating the expression of immune checkpoint (PD-L1) in NSCLC, and the upregulation of TOP2A signi cantly promotes the expression of immune checkpoint (PD-L1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PD-1/PD-L1, the CTLA-4 immune checkpoint is also critical in the response to T-cell activation. ICIs targeting CTLA-4 have been a major focus of immunotherapy development in several malignancies, including CC, with ipilimumab being the most widely researched anti-CTLA-4 monoclonal antibody for CC [158]. In the clinical trials GOG-9929 (NCT01711515) [159] and 938TiPA (NCT01693783) [160], ipilimumab demonstrated immune-modulating activity in significant T-cell population expansion as an adjuvant therapy to definitive CRT in women with locally advanced CC [159] but no significant response as a monotherapy in metastatic CC [160].…”
Section: Cervical Cancermentioning
confidence: 99%